The Influence of Learning Method and Learning Style of the Ability for English Students of Akademi Pariwisata Satu Nusa Bandar Lampung - Rara Agustin (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
The purpose of this research is to know and analyze the effects of learning method and learning style to influence the ability for English students of Akademi Pariwisata Satu Nusa Bandar Lampung. This research consisted of forty two respondent on Akademi Pariwisata Satu Nusa Bandar Lampung. In the methode do applying for collecting data by documentation study, observation and interview, and then the angket. For processing data using the multiple regression analysis to know relation indefendent variable (X1) method of learning and (X2) learning style to influence defendant variable (Y) ability of English students. Furthermore in its data analysis using SPSS Statistics 24 program. In addition, the results of these research appeared that by significant 0, 05 for two side test 2, 5% and n =42 to obtain t statistics’s table 2,023. But t from testing 2,731 for method of learning, and 3,119 for learning style therefore method of learning and learning style has positive significant influences for the ability of English students of Akademi Pariwisata Satu Nusa Bandar Lampung. This result could be explained that testing of F and testing of t statistics. F statistics’s table 3,238 but F testing 9,141 by statistics’s table. Therefore, it can be conclude that there is any positive significant influences on English students’ ability of Akademi Pariwisata Satu Nusa Bandar Lampung.